Cultural-Based Educational Policy Strategy in Revitalizing the Betawi Language in Elementary and Junior High Schools in Jakarta - Nana Yuliana; Tadjuddin Nur; Somadi Sosrohadi (Hasanuddin University, 2026)
This study aims to analyze the implementation of revitalizing the Betawi language at the elementary school (SD) and junior high school (SMP) levels in Jakarta through the integration of local culture in educational activities. The study employs a qualitative approach with a descriptive method to describe the practices of using the Betawi language in school learning contexts. Data were collected through classroom observations, interviews with teachers and students, and analysis of learning documents and school cultural activities. The results show that the policy of revitalization of the Betawi language is more effective when integrated into project-based learning, school cultural activities, and creative activities that incorporate elements of Betawi culture, such as art performances, role-playing, and daily communication practices. This approach has proven capable of increasing students’ interest, participation, and awareness of the Betawi language as part of their local cultural identity. However, its implementation of the revitalization program still faces several challenges, including the absence of a specific curriculum, limited teaching materials, lack of teacher training, and the influence of popular and global languages in students’ daily lives. Therefore, it is necessary to develop a strategy to include a structured curriculum or local content program, provide relevant teaching materials, improve teacher capacity, and utilize digital technology and social media as learning media. Sustainable policy support and collaboration among schools, government, and communities are essential factors in strengthening the revitalization of the Betawi language and maintaining the sustainability of local language as part of Jakarta’s cultural identity.